The Effect of Problem Posing Using Students' Worksheet to Improve Mathematics Communication - Latifah Angraini Siregar; E Elvis Napitupulu (Journal Mathematics Education Sigma [JMES], 2023)
Abstract. This research aims to describe the effect of problem posing model to improve mathematics communication ability. Model problem posing applied by using students’ worksheet. The research method used quasi-experiment. Design of research using control and experiment class. Technique of data collection by using pre-test and post-test. The population of this research is class VIII MTs M 09 KHA Dahlan Sipirok. The sample of research consisted of two class which are taken purposively. Data of this research were analyzed by using normality test, homogeneity test, t-test and determine category of N-Gain. Assisted by SPSS, data obtained is normal and homogeneous. The significance level of t-test is less than such that was rejected and was accepted. There is a difference of mathematic communication ability between students who taught by problem posing model and those taught direct instructions. It is suggested to apply problem posing model by using students’ worksheet to improve mathematics communication ability.Abstrak. Penelitian ini bertujuan untuk mendeskripsikan pengaruh model problem posing untuk meningkatkan kemampuan komunikasi matematika. Model problem posing diterapkan dengan menggunakan lembar kerja siswa. Metode penelitian menggunakan quasi experiment. Perancangan penelitian menggunakan kelas kontrol dan eksperimen. Teknik pengumpulan data dengan menggunakan pre-test dan post-test. Populasi penelitian ini adalah kelas VIII MTs M 09 KHA Dahlan Sipirok. Sampel penelitian terdiri dari dua kelas yang diambil secara purposive. Data penelitian ini dianalisis dengan menggunakan uji normalitas, uji homogenitas, uji-t dan menentukan kategori N-Gain. Dibantu SPSS, data yang diperoleh normal dan homogen. Tingkat signifikansi uji-t kurang dari yang ditolak dan diterima. Ada perbedaan kemampuan komunikasi matematika antara siswa yang mengajar dengan model problem posing dengan mereka yang diajarkan instruksi langsung. Disarankan untuk menerapkan model problem posing dengan menggunakan lembar kerja siswa untuk meningkatkan kemampuan komunikasi matematika.